The Role of Customer Experience and Relationship Quality in Shaping Purchase Intent, Loyalty, and Participation of IQOS Indonesia Consumers - Muhammad Arieq Haydar; Erlita Ridanasti (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The development of alternative tobacco products, specifically heat-not-burn tobacco products (HNBTs), is driving changes in consumer behavior, particularly in the context of customer experience and long-term brand relationships, amidst limited promotional regulations in Indonesia. This study aims to analyze the influence of customer experience on relationship quality, as well as the influence of relationship quality on purchase intention, loyalty intention, and consumer participation intention for IQOS in Indonesia. This study uses a quantitative approach with a survey method of 230 respondents who have tried or used IQOS, with data analysis using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The research results indicate that customer experience has a positive and significant impact on relationship quality, and relationship quality has a positive and significant impact on purchase intention, loyalty intention, and participation intention. This finding confirms that a positive customer experience plays a crucial role in building the quality of relationships that drive sustainable consumer behavior.